Historia Y Evolución De La Industria De Semiconductores Y La Integración De México En El Sector - Mercado, Alejandro Mercado; Facio, Manuel Martínez; Flores, Fernando Favila; Moya, Ana García (European Scientific Journal, ESJ, 2016)
Semiconductors and their applications, represent one of the technological revolutions with greatest impact on society, generating Industrial changes, new companies, jobs, professional careers and development of new products that have given a twist in the way of life of people around the world. This has produced an industrial war between developed countries, which dispute the first place in terms of production, import and export of semiconductors. The semiconductors industry has given way to agreements and alliances between countries; allowing México to participate on the import, export and the formation of research and development in the industry. The present research, have as an objective to review theoretically the historical evolution of the semiconductor industry and the incorporation of México in the sector.